CARA MEMBUAT DATA KOORDINAT DIJITAL DARI AREA PENAMBANGAN BATU SPLIT YANG BERSUMBER DARI DATA THEODOLITH KONVENSIONAL - Jarwanto (Nusantara Hasana Journal, 2022)
Sokkisha's conventional Theodolith units can be used for land mapping, but the results can be digitized according to the current software format. The data obtained are data on azimuth direction, optical distance, elevation which are recorded manually and processed using Microsoft Excel software. The results obtained are data that have x, y and z coordinates and are then supplemented with data that has: number, easting ("x"), northing ("y"), elevation ("z") and description or description. This data is called data abbreviated as PENZD data which is transferred first using a notepad to be entered into Autocad Landesktop 2009 software. In Autocad Landesktop 2009 PENZD data is visualized in vector form so that contours can be made or as virtual lines that have the same height and can be read by exporting it into a file with a dxf extension that can be read by other software such as Minescape, Surpac, 12 D, Terramodel or other vector-based software.